Is Two-Tier Health Care the Future? (University of Ottawa Press / Les Presses de l’Université d’Ottawa, 2024)
Canadians are deeply worried about wait times for health care. Entrepreneurial doctors and private clinics are bringing Charter challenges to existing laws restrictive of a two-tier system. They argue that Canada is an outlier among developed countries in limiting options to jump the queue.